A study on the thermal distribution of the thermoforming process for Polyphenylene Sulfite (Polyphenylene Sulfide) PPS composites towards out of autoclave activity - Razali, Nadlene; Rashid, Bushra; Sharif, Emy Aqillah; Hamdan, Hasanudin; Ramlan, Muhammad Zaid Harith; Muhammad, Noryani; Zakaria, Mohamad Shukri; Ahmad Rashidi, Syazwan (Universiti Putra Malaysia Press, 2024)
The thermoforming process is a widely utilized manufacturing technique for shaping thermoplastic materials into various products. Achieving uniform and controlled thermal distribution within the material during thermoforming is crucial to ensure high-quality products and minimize defects. This study investigates and enhances the understanding of thermal distribution in thermoforming processes through simulation analysis before it is done via experiment. This research investigates the thermal distribution in the thermoforming process of Polyphenylene Sulfide composites. The heating element distances were varied during the simulations of the thermoforming process of Polyphenylene Sulfide (PPS) composites, focusing on understanding how different distances affect the material’s deformability, dimensional accuracy, and overall quality. Three heater temperatures with three heater distances are tested. The distance between two heated surfaces is 200, 300 and 500 mm for 320o C, 360o C and 400o C heated surfaces. The desired PPS temperature (320o C) and maximum heater temperature (400o C) are parameters. The test result shows that to achieve 320o C thermoplastic temperature, we can use 385o C IR heater temperature with a heater distance of 200 mm. However, this 200 mm distance might be too close for the operation, and a larger distance might be needed. Using 300 mm or 500 mm can achieve close to 320o C if the heater temperature is set to 400o C. In conclusion, this value is a reference for the distance of the material between the heater during the fabrication process.